Descriptive Study on Nature of Perceived Stress of Mothers of Children with Autism Spectrum Disorder - A Qualitative Analysis - Menezes Ida Sylvia; N Vidya; D’Mello Laveena (International Journal of Management, Technology and Social Sciences (IJMTS), 2024)
This study examines the nature and impact of parental stress specifically among mothers of children with Autism Spectrum Disorder (ASD). Parental stress is a significant concern in families raising children with ASD due to the unique challenges associated with the condition. The study aims to explore the factors contributing to maternal stress, including caregiving demands, social support, coping mechanisms, and personal resilience. Methodologically, in-depth interviews as the mono-method approach are employed, to measure stress levels with qualitative insights into mothers’ experiences. Participants are recruited from diverse socio-economic backgrounds to ensure a comprehensive understanding of the phenomenon. Findings highlight the multifaceted nature of parental stress in this population, shedding light on the specific stressors and protective factors that influence maternal well-being. Implications for interventions and support services aimed at alleviating maternal stress and promoting family resilience are discussed based on the study’s results.